Asuhan Kebidanan Continuity of Care pada Ny. N.E Umur 30 Tahun di Puskesmas Lalowaru - Pratiwi, Wilda; Yulia Nur Khayati (Universitas Ngudi Waluyo, 2024)
According to the World Health Organization (WHO), the maternal mortality rate is still very high. In 2017, approximately 295,000 women died from complications related to pregnancy and childbirth, which means approximately 810 women die every day from preventable causes. The role of midwives is very important in reducing MMR and IMR, one of which is through continuous midwifery care. This care includes a